EFFECT OF VARIOUS PLANTING TECHNIQUES ON YIELD AND YIELD COMPONENTS OF RICE - S. Hussain; M. Ramzan; M. A. Rana; R. A. Mann; M. Akhter (Journal of Animal and Plant Sciences, 2013)
To study the effects of planting techniques on performance of rice, multilocational trials were conducted at Pindi Rattan Singh, Kot Nazir and PARC farm Kala Shah Kaku during 2009. Eight planting methods viz; drilling of soaked seed in wattar condition, drilling on beds and furrow, drilling on beds, Planting on beds & furrow, transplanting on beds, line transplanting in a well puddled soil, conventional transplanting and parachute transplanting were tested. The highest plant height (123.70 cm), productive tillers (264.67/m2), paddy yield (3.90 t/ha) and cost benefit ratio (1.29) were observed in line transplanting method. Minimum paddy yields (3.07 t/ha) were obtained from drilling on beds. The highest profit was obtained from line transplanting so it was the method ensuring maximum benefit to the producer. Key words: Planting techniques, Rice, Production, cost benefit.
Keywords: Planting techniques; Rice; Production; cost benefit